Differential Transcriptome Analysis Reveals Genes Related to Low- and High-Temperature Stress in the Fall Armyworm, Spodoptera frugiperda - Vatanparast, Mohammad; Park, Youngjin (Frontiers in Physiology, 2022)
The fall armyworm (FAW), Spodoptera frugiperda, is regarded as one of the world's most harmful plant pests. This research examines the molecular response processes of FAW to low temperature (4°C) and high temperature (40°C) when gene expression is compared to controls (25°C). A total of 211,967 unigenes were collected, at least 14,338 of which were annotated with gene descriptions, gene ontology terms, and metabolic pathways. There were 50 Gene Ontology (GO) functional sub-groups and 21 EggNOG words as a result. Differentially expresses genes (DEGs) with log2FC≥2 were identified and compared at various temperatures. In comparison to the 25°C treated group, we discovered 199 and 1,248 individual DEGs co-regulated at 4 and 40°C, respectively. Comparing transcriptome profiles for differential gene expression revealed a number of DEGs, including cytochrome P450, odorant binding proteins (OBP), and immune system genes previously implicated in cold and high temperature stresses. The enrichment pathways were identified using Kyoto Encyclopedia of Genes and Genomics (KEGG) analysis, and heatmaps of similar unigenes from both treatment groups (T4 and T40) were plotted. We used reverse transcription quantitative PCR (RT-qPCR) to confirm the RNA-seq data on 10 up- and down-regulated DEGs. These findings provide a foundation for future understanding of FAW adaptation mechanisms and the underlying basis underlying the response to low and high temperatures.